Comparison of Scoring Systems in Pediatric Mini-Percutaneous Nephrolithotomy - TOSUN, MUHAMMED; Utangac, Mehmet Mazhar; Tepeler, Abdulkadir; Daggulli, Mansur; Tosun, Muhammed; Dede, Onur; Armagan, Abdullah (My University, 2016)
OBJECTIVE To apply urolithiasis scoring systems to the pediatric miniperc procedure and to compare their predictive capability for postoperative outcomes.